2013
DOI: 10.1371/journal.pone.0057222
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Baseline BMI on Glycemic Control and Weight Change with Metformin Monotherapy in Chinese Type 2 Diabetes Patients: Phase IV Open-Label Trial

Abstract: BackgroundDifferences exist between treatment recommendations regarding the choice of metformin as first-line therapy for type 2 diabetes patients according to body mass index (BMI). This study compared the efficacy of metformin monotherapy among normal-weight, overweight, and obese patients with newly diagnosed type 2 diabetes.MethodsIn this prospective, multicenter, open-label study in China, patients aged 23–77 years were enrolled 1∶1:1 according to baseline BMI: normal-weight (BMI 18.5−23.9 kg/m2; n = 125)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 18 publications
6
32
0
1
Order By: Relevance
“…Similar to other studies [35], BMI and other clinical characteristics were not associated with glycemic control, total cholesterol, or LDL cholesterol. However, increased BMI was associated with increased TAG levels.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other studies [35], BMI and other clinical characteristics were not associated with glycemic control, total cholesterol, or LDL cholesterol. However, increased BMI was associated with increased TAG levels.…”
Section: Discussionsupporting
confidence: 88%
“…Besides the possible genetic reason, so far, obvious reason is few, but similar results were reported in some trials or meta-analyses of type 2 diabetes patients who were treated with SUs, AGIs, or metformin, DPP-4 inhibitors, GLP-1 receptor agonists.In SU treated patients, a subgroup analysis from the ADVANCE study indicated that [2], the mean HbA1c reduction between the group of baseline BMI <28 and baseline BMI ≥28 suggested no significant difference. In metformin or AGI treated patients, the results from a prospective, multicenter, open-label study in newly diagnosed Chinese type 2 diabetes [7], indicated that baseline BMI had no impact on glycemic control, weight change or other efficacy measures. Another post-hoc analysis [14] of a randomized controlled trial also concluded that both acarbose and metformin similarly decreased the HbA1c levels regardless of the BMI status.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Japanese type 2 diabetes patients with sitagliptin treatment [6], multiple regression analysis indicated that baseline BMI was independently correlated with HbA1c reduction at 3 months (p < 0.001). Contrarily, in a trial [7] comparing the efficacy of metformin monotherapy among normal-weight, overweight, and obese patients with newly diagnosed type 2 diabetes, Ji reported that baseline BMI had no impact on glycemic control. Additionally, some meta-analyses [8] indicated that baseline BMI might be associated with the different efficacies of glucose changes for some hypoglycemic treatments, while others did not [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The between-group difference is within the bounds of natural variation, as reflected by the SDs and the mean baseline HbA 1c levels of 7.0-8.3% reported in other observational and phase IV studies or surveys. [15][16][17] The comparison of UK DSP and HSFE diabetes data, which was performed to substantiate the findings of the Chinese comparison, also provided evidence for the representativeness of the DSP, with equivalence in many of variables. Although equivalence was not demonstrated for some, including patient age and time since diagnosis, this may reflect different characteristics of presenting patients in the DSP versus the randomly selected HSFE group.…”
Section: Discussionmentioning
confidence: 91%